Carbon losses from all soils across England and Wales 1978−200 - Bellamy, Patricia H.; Loveland, Peter J.; Bradley, R. Ian; Lark, R. Murray; Kirk, Guy J. D. (Nature Publishing Group, 2005)
Most terrestrial carbon is held in soils, more than twice as much as in vegetation or the atmosphere 1 , and changes in soil carbon content can have a large effect on the global carbon budget. The possibility that climate change is being reinforced by increased carbon dioxide emissions from soils with rising temperature is the subject of a continuing debate 29 . But to date evidence for the suggested feedback mechanism has come solely from small-scale laboratory and field experiments and modelling studies 29 . Here we use data from the National Soil Inventory of England and Wales obtained between 1978 and 2003 to show that carbon was lost from soils across England and Wales over the survey period at a mean rate of 0.6 per cent per year (relative to the existing soil carbon content). We find that the relative rate of carbon loss increased with soil carbon content and was more than two per cent per year in soils with carbon contents greater than 100 grams per kilogram. The relationship between rate of loss and carbon content held across the whole country and across all forms of land use suggesting a link to climate change. Our findings indicate that losses of soil carbon in England and Wales, and by inference other temperate regions, are likely to have been offsetting absorption of carbon by terrestrial si